1997
DOI: 10.1086/304535
|View full text |Cite
|
Sign up to set email alerts
|

The MACHO Project Large Magellanic Cloud Microlensing Results from the First Two Years and the Nature of the Galactic Dark Halo

Abstract: The MACHO Project is a search for dark matter in the form of massive compact halo objects (MACHOs). Photometric monitoring of millions of stars in the Large Magellanic Cloud (LMC), Small Magellanic Cloud (SMC), and Galactic bulge is used to search for gravitational microlensing events caused by these otherwise invisible objects. Analysis of the Ðrst 2.1 yr of photometry of 8.5 million stars in the LMC reveals eight candidate microlensing events. This is substantially more than the number expected (D1.1) from l… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

26
528
1
2

Year Published

2001
2001
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 500 publications
(557 citation statements)
references
References 57 publications
26
528
1
2
Order By: Relevance
“…The suggestion of the MACHO team (Alcock et al 1997(Alcock et al , 2000 that white dwarfs contribute significantly to the mass budget of the Galactic halo has motivated a large number of observational searches (Knox et al 1999;Ibata et al 1999;Oppenheimer et al 2001;Majewski & Siegel 2002;Nelson et al 2002) for these elusive white dwarfs. Also several theoretical works (Reylé et al 2001;Flynn et al 2003) have analyzed this possibility.…”
Section: Introductionmentioning
confidence: 99%
“…The suggestion of the MACHO team (Alcock et al 1997(Alcock et al , 2000 that white dwarfs contribute significantly to the mass budget of the Galactic halo has motivated a large number of observational searches (Knox et al 1999;Ibata et al 1999;Oppenheimer et al 2001;Majewski & Siegel 2002;Nelson et al 2002) for these elusive white dwarfs. Also several theoretical works (Reylé et al 2001;Flynn et al 2003) have analyzed this possibility.…”
Section: Introductionmentioning
confidence: 99%
“…Microlensing experiments like MACHO (Alcock et al (1997); Alcock et al (2000)), EROS (Afonso et al (2000); Lasserre et al (2000)) and OGLE (Udalski et al (1998)), found that the events detected towards the galactic bulge and the LMC were consistent with the lensing objects being small (in size) stars, with a mass of ∼ 0.6M , a very good match to a WD star. These faint objects could account for about 20 % to 30 % of the dark matter in the galactic halo, in this case the prime candidates are faint Halo WDs.…”
Section: Renewed Interest In Low-luminosity Starsmentioning
confidence: 96%
“…The search, in this case, was motivated by the results of the microlensing experiments (MACHO (Alcock et al (1997); Alcock et al (2000)), EROS (Afonso et al (2000); Lasserre et al (2000)) and OGLE (Udalski et al (1998)), that suggested that up to 30% of the Halo baryonic dark matter could be in the form of WDs. So far, the observed density of matter in halo WDs has only an upper limit of ρ halo w d < 4 × 10 −5 M pc −3 (Harris et al (2006)).…”
Section: Cool White Dwarfsmentioning
confidence: 99%
“…Alcock et al 1997a;De Paolis et al 1996;Melchior et al 1998). These observations have led to the conclusion that about 50% of the galactic dark matter is in the form of MACHOs (Massive Astrophysical Compact Halo Objects) with mass m 0.4 M .…”
Section: Introductionmentioning
confidence: 99%
“…We assume that halo lens objects have a mass 0.4 M and constitute a fraction f 0.5 of the halo dark matter as shown by microlensing observations (see e.g. Alcock et al 1997a…”
Section: Introductionmentioning
confidence: 99%